LAKE-BSG: Lightweight authenticated key exchange scheme for blockchain-enabled smart grids. (August 2022) - Badshah, Akhtar; Waqas, Muhammad; Abbas, Ghulam; Muhammad, Fazal; Abbas, Ziaul Haq; Vimal, S.; Bilal, Muhammad
Abstract: The Smart grid employs information and communication networks to collect data on energy production and consumption, and then utilize it to improve efficiency, reliability, economic benefit, power generation, and distribution sustainability. However, in SG networks the components communicate over insecure public channels, raising severe security concerns. Likewise, the security challenge is growing more difficult with the introduction of virtual solutions in SG networks. Thus, we devise a new scheme, named lightweight authenticated key exchange scheme for a blockchain-enabled SG environment (LAKE-BSG), which permits secure communication among smart meters (SMs) and service providers (SPs). In the proposed scheme, data is kept secured in a blockchain network. SPs are liable for verifying new blocks in the private blockchain through a consensus algorithm. We provide a detailed security analysis of LAKE-BSG through informal security analysis, formal security analysis using the real oracle model, and formal security verification using the Scyther tool. The results demonstrate that the devised scheme is resilient towards various security attacks in an SG environment. Furthermore, an exhaustive comparative analysis reveals that LAKE-BSG is efficient in terms of communication and computation overheads and provides additional security and functionality features.